Search and evaluation of pharmacodynamic and pharmacokinetic parameters of selective blocker of TRPA 1 ion channels from the group of substituted pyrazinopyrimidinones - Evgeniya А. Beskhmelnitsyna; Dmitriy V. Kravchenko; Lev N. Sernov; Irina N. Dolzhikova; Tatyana V. Avtina; Alexandr L. Kulikov; Darya V. Rozhnova; Vladimir I. Yakushev; Mikhail A. Martynov (Belgorod National Research University, 2018)
Introduction. Doctors of almost all specialties have to deal with the problem of pain and its relief. According to the literature, almost 30 million people daily take analgesics from the group of non-opioid analgesics, but in more than half of them 4-6 hours after taking the medication, the severity of pain is unchanged. Objective. to search for the most active molecules potential selective inhibitors of the TRPA1 ion channel with further investigation of their pharmacodynamic effects, toxicological safety, pharmacokinetic parameters and organ distribution, as well as to assess their impact on the psychoemotional state, general locomotor activity levels and anxiety in laboratory animals. Materials and methods. According to the results of in vitro tests, the most active molecule under code ZC02-0012 was selected from the pool of candidates. Further its analgesic activity was evaluated using an acetic acid-induced writhing test and a hot plate test; its anti-inflammatory activity was studied in the acute exudative paw edema model; in the open field and elevated plus-maze tests the influence of ZC02-0012 on the general locomotor activity levels and the anxiety of the laboratory animals was studied. The pharmacokinetic parameters and organ distribution of the substance ZC02-0012 were studied using a liquid chromatograph with an operating pressure range of 0-60 mPa (Thermo Scientific Dionex UltiMate 3000). Results and discussion. According to the results of in vitro tests, it was found that IC50 of the TRPA1 selective inhibitor under laboratory code ZC02-0012 was 91.3 nmol. The preclinical studies showed that ZC02-0012 possessed pronounced analgesic and anti-inflammatory activities and absence of the influence on the behavior and anxiety of the laboratory animals. Absolute bioavailability of ZC02-0012 in rabbits was 47%, while ZC02-0012 was intensely distributed into organs and tissues with a high level of blood circulation. The highest content of ZC02-0012 is typical of liver, kidneys and lungs, the lowest - for muscle tissue. Most of the substance is undergone rapid biotransformation and excreted as metabolites.